2023
DOI: 10.1055/a-2051-8544
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effectiveness of Systemic Inflammatory Indices in the Diagnosis of Respiratory Distress Syndrome in Preterm with Gestational Age of ≤32 Weeks

Abstract: Objective: It is not yet known whether systemic inflammatory indices affect the development of respiratory distress syndrome (RDS) in premature infants. We aimed to evaluate the relationship between systemic inflammatory indices obtained on the first day of life and the development of RDS in premature infants. Study Design: Premature infants with gestational age of ≤32 weeks were included in the study. Six systemic inflammatory indices involving neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
(84 reference statements)
0
2
0
Order By: Relevance
“…In our study, GA, BW, leukocyte parameters and systemic inflammatory indices were similar in both genders, as well as the frequency of RDS and BPD was higher in males. In a newly published study, it has been shown that high SII values may be a predictor for RDS in preterms ≤32 weeks of gestational age 40 . In another recent study, it has been reported that high SIRI values for both at birth and at the 36 th week of postmenstrual age could be a predictor marker for moderate to severe BPD in prematures <32 weeks of gestational age 41 .…”
Section: Resultsmentioning
confidence: 99%
“…In our study, GA, BW, leukocyte parameters and systemic inflammatory indices were similar in both genders, as well as the frequency of RDS and BPD was higher in males. In a newly published study, it has been shown that high SII values may be a predictor for RDS in preterms ≤32 weeks of gestational age 40 . In another recent study, it has been reported that high SIRI values for both at birth and at the 36 th week of postmenstrual age could be a predictor marker for moderate to severe BPD in prematures <32 weeks of gestational age 41 .…”
Section: Resultsmentioning
confidence: 99%
“…PIV is a marker that integrates various markers of inflammation and immune system and has shown promise as a predictor of prognosis in different diseases [15,16]. It has been studied in various cancer types, including esophageal, colorectal, and breast cancer [11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…PIV has been proposed as a biomarker in other medical conditions as well. It has been evaluated in the diagnosis of respiratory distress syndrome in preterm infants [ 15 ]. In the field of pediatric acute-onset neuropsychiatric syndrome (PANS), which is associated with immune abnormalities, PIV has been studied in the context of treatment outcomes [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our results, the AUC value of SII for the predictivity of mortality in VLBW infants was 0.844, and the cutoff value was ≤28.87. It has been reported that an SII level ≥78.2 after birth may be a risk factor for the development of RDS in preterms ≤32 weeks of gestation 15 . It was found that the high SIRI value could predict moderate to severe BPD in preterm infants 16 .…”
Section: Discussionmentioning
confidence: 99%